Effects of Lactobacillus plantarum on the Fermentation Profile and Microbiological Composition of Wheat Fermented Silage Under the Freezing and Thawing Low Temperatures - Zhang, Miao; Wang, Lei; Wu, Guofang; Wang, Xing; Lv, Haoxin; Chen, Jun; Liu, Yuan; Pang, Huili; Tan, Zhongfang (Frontiers in Microbiology, 2021)
The corruption and/or poor quality of silages caused by low temperature and freeze-thaw conditions makes it imperative to identify effective starters and low temperature silage fermentation technology that can assist the animal feed industry and improve livestock productivity. The effect of L. plantarum QZ227 on the wheat silage quality was evaluated under conditions at constant low temperatures followed by repeated freezing and thawing at low temperatures. QZ227 became the predominant strain in 10 days and underwent a more intensive lactic acid bacteria fermentation than CK. QZ227 accumulated more lactic acid, but lower pH and ammonia nitrogen in the fermentation.. During the repeated freezing and thawing process, the accumulated lactic acid in the silage fermented by QZ227 remained relatively stable. Relative to CK, QZ227 reduced the abundance of fungal pathogens in silage at a constant 5 °C, including Aspergillus, Sporidiobolaceae, Hypocreaceae, Pleosporales, Cutaneotrichosporon, Alternaria, and Cystobasidiomycetes. Under varying low temperature conditions from days 40 to days 60, QZ227 reduced the pathogenic abundance of fungi such as Pichia, Aspergillus, Agaricales, and Plectosphaerella. QZ227 also reduced the pathogenic abundance of Mucoromycota after the silage had been exposed to oxygen. In conclusion, QZ227 can be used as a silage additive in the fermentation process at both constant and variable low temperatures to ensure fast and vigorous fermentation because it promotes the rapid accumulation of lactic acid, and reduces pH values and aerobic corruption compared to the CK.